2013
DOI: 10.12693/aphyspola.124.102
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of CsSnM3(M = Cl, Br, I): A First Principle Study

Abstract: First principle calculations are carried out to investigate the structural, electronic and optical properties of cubic perovskites CsSnM3 (M = Cl, Br, I). The theoretically calculated lattice constants are found to be in good agreement with the experimentally measured values as compared to previous calculations. It is found that these perovskites are direct band gap semiconductors. The electrons densities reveal strong ionic bonding between Cs and halide cations while strong covalent bonding between Sn and hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(39 citation statements)
references
References 33 publications
3
36
0
Order By: Relevance
“…Therefore, pressured-induced CsSnCl 3 metal halide exhibits higher static value of dielectric constant as band gap is decreased (see electronic properties segment) with pressure. The imaginary part of the dielectric function is associated directly with the material band structure and explains its absorption nature 13 . The peaks of the imaginary part of dielectric functions are increased in a prominent way with pressure and shift to the low energy region, which justifies the result of absorption spectra as illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, pressured-induced CsSnCl 3 metal halide exhibits higher static value of dielectric constant as band gap is decreased (see electronic properties segment) with pressure. The imaginary part of the dielectric function is associated directly with the material band structure and explains its absorption nature 13 . The peaks of the imaginary part of dielectric functions are increased in a prominent way with pressure and shift to the low energy region, which justifies the result of absorption spectra as illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the environment contamination and world-wide energy crisis, clean and sustainable energy sources have taken great attention. Therefore, a large number of experimental and theoretical works have been performed by replacing Pb with a suitable metal cation in the last few years 10 13 . The study of mechanical properties reported by Roknuzzaman et al 10 demonstrates that the non-toxic CsSnCl 3 perovskite has ductility entity but the halide perovskite semiconductor shows large band gap value (2.8 eV) 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, its high hole mobility, due to the small hole effective mass, make it an excellent solid-state replacement for the electrolyte in dye-sensitized solar cells [15]. The cubic phase of CsSnI 3 also has interesting structural and optical properties, with high absorption coefficients at infrared, visible, and ultraviolet wavelengths, making it useful for optical and optoelectronic applications working within this range of the electromagnetic spectrum [16]. By exploring the Cs position offsets and lattice expansion [2], it has been predicted that the Bα structure is never an energy minimum, and can be deformed to the Bβ state without any energy barriers [2].…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing ionic size of the anions from Cl to Br to I, an increase in the lattice constant has been observed 45. However, upon proceeding down the group from Cl to I, a shift to longer wavelengths is observed in the electronic absorption spectra for Pb halide perovskite.…”
Section: Organic‐inorganic Hybrid Perovskite Materialsmentioning
confidence: 99%